Analisis Kebutuhan Media Pembelajaran Augmented Reality untuk Meningkatkan Motivasi Belajar Sejarah Siswa SMA - Andana, Avelza; Yefterson, Ridho Bayu (Jurusan Sejarah FIS UNP, 2025)
This research is motivated by the low motivation and learning outcomes in history among students of class XI F6 at SMA Negeri 3 Pariaman, as reflected in their passive classroom participation, monotonus use of instructional media, and an average test score of only 58%, indicating the urgent need for a more engaging and interactive learning tool to improve historical understanding and student engagement. The objective of this study is to analyze the necessity of developing an Augmented Reality (AR) based learning media tailored to student conditional and the school available infrastructure, as well as to explore its potential effectiveness in supporting the history learning process. The research employed a descriptive qualitiative method using classroom observations interviews review as data collection technuiqes. The findings revealed that teachers require more varied and interactive media, student have access to personal digital devices, and the school provides adequate technological support including projectors and internet access. The onclusion of this study it that Augmented Reality based learning media has significant potential as an innovative solution to enhance students motivation and learning outcomes in history by providing a more engaging, visual, and interactive learning experience.